Multi-solid waste collaborative production of clinker-free cemented iron tailings backfill material with ultra-low binder-tailing ratio. (27th February 2023) - He, Xingyang; Li, Weilong; Yang, Jin; Su, Ying; Zhang, Yunning; Zeng, Jingyi; Dai, Fei; Tan, Hongbo
Highlights: A preparation process of clinker-free cemented iron tailings backfill material with ultra-low binder-tailing ratio. Compressive strength of clinker-free backfill material with ultra-low binder-tailing ratio was up to 3.7 MPa. Compressive strength of prepared clinker-free backfill material is significantly higher than previously reported work. Hemihydrate gypsum is more efficient to improve compressive strength, settling resistance and water resistance. Abstract: In order to improve the beneficiation efficiency, the ore have been ground finer or even exceed the fineness of cement. The cost of the material rises as a result of ordinary cementitious materials being unable to meet the ultra-fine backfill material needs. In this work, ground granulated blast-furnace slag (GGBS) was disposed by wet-milling process, and its median particle size (D50 ) reached 1.94 μm, which effectively improved its cementing efficiency. Based on this, a clinker-free cemented iron tailings backfill material with ultra-low binder-tailing ratio (1:12) was prepared with 28 d compressive strength up to 3.7 MPa, which is significantly higher than previously reported work. HPG makes it simpler to produce backfill materials with superior compressive strength, settling ratio and water resistance than PG. At the same time, the workability, mechanical properties and ion leaching of the clinker-free backfill material reached the specification requirements. Each cubic meter of backfill material can absorb iron tailings up to 1699.92 kg/m 3 .